Upaya Meningkatkan Hasil Belajar Servis Atas Permainan Bolavoli Menggunakan Model Pembelajaran Example Non-Example pada Siswa Kelas V Sdit Nurul Islam Tahun Ajaran 2022/2023 - Saputra, Ahmad Rezal; Muharram, Nur Ahmad; Slamet Junaidi, Slamet Junaidi (Jurnal Kridatama Sains dan Teknologi, 2022)
The purpose of this study was to improve the learning outcomes of serving in volleyball in class V students at SDIT Nurul Islam for the 2022/2023 Academic Year. This research is a Classroom Action Research (CAR). This research was conducted in two cycles and consisted of four stages in each cycle, namely planning, action, observation and reflection. The subjects in this Classroom Action Research were class V students at SDIT Nurul Islam for the 2022/2023 Academic Year, with a total of 16 students consisting of 11 male students and 5 female students. Sources of data in this study came from students, researchers and teachers who acted as collaborators. Data collection techniques using tests and observations. Data validity uses data triangulation techniques. This classroom action research is a percentage to see trends that occur in learning activities. The results of the analysis show that using the example non-example learning model can improve learning outcomes for serving volleyball from pre-cycle to cycle I and cycle I to cycle II. From the results of the analysis obtained an increase in service learning outcomes for volleyball games shown by students in cycle I cognitive aspects showed an increase of 27.08% where there were 9 students or 77.08% included in the complete category while for psychomotor aspects showed an increase of 18, 75% where there are 10 students or 62.50% fall into the complete category. In cycle II the improvement of student learning outcomes is better. Cognitive aspects increased by 4.17% from the first cycle and 31.25% from the pre-cycle, while the psychomotor aspects increased by 25.00% from the first cycle and 43.75% from the pre-cycle. In the second cycle of the cognitive aspect there were 13 students or 81.25% in the complete category, 3 students or 18.75% of students in the incomplete category and for the psychomotor aspect there were 14 students or 87.50% in the complete category, 2 students or 12.50% of students are in the incomplete category. Based on the results of the research, it can be concluded that: the application of the example non-example learning model can improve the service learning outcomes for volleyball games in class V SDIT Nurul Islam Academic Year 2022/2023. Keywords: service, volleyball, Classroom Action Research